Some unique fruits for home garden - Tripathi, Prakash Chandra (Indian Horticulture, 2021)
India has a rich and varied heritage of biodiversity, encompassing a wide spectrum of habitats from tropical rainforests to alpine vegetation and from temperate forests to coastal wetlands. Several fruit plant species have originated in Indian subcontinent. Apart from indigenous fruits, several fruits were introduced in India from South America, Africa, Europe, South East Asian countries during last four centuries. Some of the unique minor fruits which are suitable for the backyard garden in tropical and sub-tropical regions are described herewith.